2021
DOI: 10.29333/mathsciteacher/11075
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation and Assessment of a Web-Based Ethnomathematics Instructional Content Repository for Mathematics Teachers in Benue State, Nigeria

Abstract: This study developed and assessed a web-based ethnomathematics instructional content repository for pre-service and in-service mathematics teachers in Benue State, Nigeria. The study adopted a developmental research design to systematically build and evaluate the educational intervention as a solution to complex problems in mathematics education practice. The development was achieved using WordPress Version 5.4, hosted online at https://villagemath.net on Linux OS server running with cPanel v80.p (Build 20), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, it gives them the opportunity to spend more time on their assigned tasks and gives them more time to prepare and review the lesson material outside of class. This finding agrees with Abah, Anyagh, & Age (2017), who observed that flipped learning stimulates students' curiosity, engagement and enlightenment. The study by Akingbemisilu (2017) revealed that flipped learning has an impact on students' academic development in biology; and the study by Charles-Ogan & Williams (2015) revealed similar results in mathematics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, it gives them the opportunity to spend more time on their assigned tasks and gives them more time to prepare and review the lesson material outside of class. This finding agrees with Abah, Anyagh, & Age (2017), who observed that flipped learning stimulates students' curiosity, engagement and enlightenment. The study by Akingbemisilu (2017) revealed that flipped learning has an impact on students' academic development in biology; and the study by Charles-Ogan & Williams (2015) revealed similar results in mathematics.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, it may equally be profiting to enhance this method with technology-based instructions that could actively engage students in instructional process and help them in gaining mastery of the contents. This is in connection with studies which have shown that technology proves to be helpful in engaging students in learning mathematics and also found useful to demystify abstract concepts in Mathematics (Oyarinde & Komolafe, 2019;Olumuyiwa, 2019;Abah, Anyagh, & Age, 2017;Esperanza, Fabian &Toto, 2016;Remalyn, 2016;Charles-Ogan & Williams, 2015). In this regard, the flipped learning approach among other modern means may be useful.…”
Section: Introductionsupporting
confidence: 56%
“…Ethnomathematics is an effective approach to learning mathematics (Sunzuma et al, 2021). Also, the ethnomathematics approach is to train students in conceptual understanding, procedural fluency, strategic competence, adaptive reasoning, and productive dispositions (Abah et al, 2021).…”
Section: Contribution To the Literaturementioning
confidence: 99%